PELATIHAN PENGGUNAAN LIVE WORSHEETS SEBAGAI LKPD INTERAKTIF DENGAN PENEKANAN PADA TIGA LEVEL REPRESENTASI KIMIA BAGI GURU KIMIA DI SMAN 1 LEMBAH GUMANTI DAN SMA DI KABUPATEN SOLOK BAGIAN SELATAN - Nizar, Umar Kalmar; Azhar, Minda; Mukhaiyar, Riki; Zulhendra, Zulhendra; Suryelita, Suryelita; Ningsih, Sherly Kasuma Warda (Pelita Eksakta, 2024)
SMA Negeri 1 Lembah Gumanti is one of the schools in Southern Solok Regency that’s actively spurring the development of its school by completing the infrastructure and quality of education for both students and teachers. ICT training especially for teachers to support the quality learning process. One of the uses of this facility is to create interactive LKPD on LiveWorksheets. The purpose of the service activity is to increase the knowledge and skills of chemistry teachers using various learning resources on websites on the internet, increase chemistry teachers' knowledge of the three levels of representation and their interconnections, increase chemistry teachers' knowledge and skills in combining learning resources for making interactive LKPD on the LiveWorksheets web with an emphasis on the three levels of chemical representation. The methods used in this activity are lecture, demonstration and practice. Training participants were asked to present the results of their activities.